Effect of Cooperative Learning Method on Academic Achievement in Mathematics of 8th Grade Students of Jabalpur District - Upadhyaya, Himani (International Journal of Advanced Research in Peace, Harmony and Education; Vol 7 No 2 (2022): International Journal of Advanced Research in Peace, Harmony & Education, 2022)
The main objective of the study was to study Gender and Type School wise effect of Cooperative Learning Method on Academic Achievement in Mathematics of 8th grade students. For achieving the objectives Investigator selected two co- educations, CBSE School of Jabalpur district (M.P.), out of 250 students of 8th grade, 108 students were selected as a sample through purposeful sampling. Pre- Test and Post-Test experimental research method (10 days treatment) and 2 x 2 x 2 factorial design ANOVA was used. The result revealed that are significant effect for individual effect of method and interactional effect of Method, Type of School and Gender at 0.01 & 0.05 level of significant, respectively. How to cite this article:  Upadhayaya H. “Effect of Cooperative Learning Method on Academic Achievement in Mathematics of 8th Grade Students of Jabalpur District”. Int J Adv Res Peace Harm Edu 2022; 7(2): 6-10.